Antimicrobial Resistance and Biofilm-Forming Ability in ESBL-Producing and Non-ESBL-Producing Escherichia coli and Klebsiella pneumoniae Isolated from Canine Urinary Samples from Italy - Alessia Facchin; Joel Filipe; Irene Mauri; Filippo Tagliasacchi; Guido Grilli; Tiziana Vitiello; Gabriele Ratti; Laura Musa; Martina Penati; Paola Scarpa; Stefania Lauzi (Antibiotics)
Background: In dogs, bacterial urinary tract infections are a frequent cause of antimicrobial prescription, increasing the risk of selecting antibiotic-resistant bacteria. This study analyzed resistance patterns, the presence of extended-spectrum β-lactamases (ESBLs) and biofilm-forming capacity in E. coli and K. pneumoniae previously isolated from urine samples collected from 133 selected dogs admitted to the Veterinary Teaching Hospital of Milan, Italy, in 2021 and 2023. Methods: The E. coli and K. pneumoniae isolates were bacteriologically and genetically analyzed. Results: Overall, 53/133 (39.8%) samples had a positive microbiological culture. Thirty-four E. coli/K. pneumoniae isolates were detected, accounting for 26.5% of the examined samples. The 34 isolates included 28 E. coli and 6 K. pneumoniae. Four (11.8%) were ESBL-producing bacteria, all supported by blaCTX-M gene belonging to group 1. The K. pneumoniae isolates were significantly associated with ESBL production (p < 0.05). MIC analysis showed 11 (32.4%) multidrug-resistant isolates. Biofilm-forming capacity was observed in 23 (67.6%) isolates, regardless of bacterial species, including 20 weakly and 3 moderately adherent bacteria. All moderate biofilm producers were K. pneumoniae. Multidrug resistance (MDR) was significantly more present in strains with moderate biofilm-forming ability compared to strains with weak ability to form biofilm (p < 0.05). E. coli was confirmed as the most commonly identified urinary isolate in dogs. Conclusions: The high presence of ESBL producers and MDR in K. pneumoniae suggests mandatory in vitro susceptibility testing in the presence of this bacterium in dogs with UTI. The association of moderate biofilm production with MDR highlights the need for monitoring and surveillance of bacterial prevalence and resistance patterns of urinary isolates in dogs.